Women's Rights from an Islamic and Western Perspective: "Relevance in the Modern Era" - Aisyah Nur Rahmah; Fatimah; Mufidah Nur Karimah (al-Afkar, Journal For Islamic Studies, 2026)
The role of women in society has undergone significant changes in the era of globalization. This article examines women's rights from Islamic and Western perspectives, highlighting the importance of freedom of speech, economic rights, and access to education as fundamental to achieving gender equality. Women's active participation in politics and the economy allows them to voice important issues and contribute to broader social change. The Islamic perspective emphasizes the obligation to seek knowledge for all individuals, regardless of gender, while the Western approach focuses on individual freedom and non-discrimination. Understanding these two perspectives helps us understand the relevance and challenges women face in fighting for their rights in the modern world. This research aims to provide a deeper understanding of women's position and encourage further discussion on gender equality across various fields.